Daemons, Cups of Forgetfulness and Eternity of the Soul in Irenaeus’ Adversus haereses 2.33-34 - Jonatan Cornish Simons Camacho (Patristica et Mediævalia, 2024)
In Adversus haereses 2.33-34, Irenaeus rejects the Platonic view of the pre-existence of the soul, and his tale of a daemon who serves up the drink from the Lethe, the river of forgetfulness. Irenaeus’ argument appears in the context of a larger polemic against the Carpocratian view of education and recollection, so it appropriately draws from philosophical discussions on education and recollection. When Irenaeus’ opposes the Platonic myth, his argument reflects Strato of Lampsacus, a Peripatetic philosopher. I will highlight the parallels between them, particularly in their description of the soul as participating in life rather than being life itself, an affirmation that has created some contention within studies of Irenaeus’ theology. Finally, I suggest that this dependence in Book 2 of Adversus haereses continues in one of Irenaeus’s most famous descriptions of participation in haer. 4.20.5, for Irenaeus uses the same metaphor of light and the same verb as Strato. In addition to studying the parallels between Irenaeus and Strato, which has not been done yet, my main contribution is to suggest that Strato’s influence should be recognized in the famous Irenaeus’s view of participation.